An RNA Sequencing Transcriptome Analysis of Grasspea (Lathyrus sativus L.) and Development of SSR and KASP Markers - Hao, Xiaopeng; Yang, Tao; Liu, Rong; Hu, Jinguo; Yao, Yang; Burlyaeva, Marina; Wang, Yan; Ren, Guixing; Zhang, Hongyan; Wang, Dong; Chang, Jianwu; Zong, Xuxiao (Frontiers in Plant Science, 2017)
Grasspea (Lathyrus sativus L., 2n=14) has great agronomic potential because of its ability to survive under extreme conditions, such as drought and flood. However, this legume is less investigated because of its sparse genomic resources and very slow breeding process. In this study, 570 million quality-filtered and trimmed cDNA sequence reads with total length of over 82 billion bp were obtained using the Illumina NextSeqTM 500 platform. Approximately two million contigs and 142,053 transcripts were assembled from our RNA-Seq data, which resulted in 27,431 unigenes with an average length of 1,250 bp and maximum length of 48,515 bp. The unigenes were of high-quality. For example, the stay-green (SGR) gene of grasspea was aligned with the SGR gene of pea with high similarity. Among these unigenes, 3,204 EST-SSR primers were designed, 284 of which were randomly chosen for validation. Of these validated unigenes, 87 (30.6%) EST-SSR primers produced polymorphic amplicons among 43 grasspea accessions selected from different geographical locations. Meanwhile, 146,406 SNPs were screened and 50 SNP loci were randomly chosen for the kompetitive allele-specific PCR (KASP) validation. Over 80% (42) SNP loci were successfully transformed to KASP markers. Comparison of the dendrograms according to the SSR and KASP markers showed that the different marker systems are partially consistent with the dendrogram constructed in our study.